Antioxidant activity, total flavonoid, and total tannin content of ethanol extract of avocado peel (Persea americana Mill.) - Rini Isromarina; Doddy Rusli; Deva Ulan Sari (Universitas Islam Indonesia, 2022)
Background: Avocado is a plant that can grow in tropical climates. In general, people only consume the fruit while the skin and seeds are not used. Avocado fruit, skin and seeds contain secondary metabolites such as flavonoids and tannins which have antioxidant activity. Objective: To determine antioxidant activity, total flavonoid, and total tannin content of the ethanol extract of avocado peel. Methods: P. americana Mill. was collected from Lubuk Linggau, South Sumatra. The ethanol extract of P. americana Mill. peel obtained by maceration with ethanol. Qualitative analysis of flavonoids using Mg and HCl while tannins using FeCl3. Determination of total flavonoid content was carried out with AlCl3 reagent and Folin-Ciocalteu reagent to determine the total tannin content and was measured by a UV-Vis Spectrophotometer. Determination of antioxidant activity using the DPPH method.Result: The results of the qualitative analysis showed that ethanol extract of avocado peel contained flavonoids and tannins. It also had antioxidant activity with IC50 of 41,93 µg/mL. The total flavonoid and tannin content of it were 125,01 mgQE/g extract and 53,82 mgTAE/g extract respectively. Conclusion: Ethanol extract of avocado peel had antioxidant activity, while the total flavonoid compounds was higher than the total tannins.Keywords: antioxidant, DPPH, total flavonoid, total tannins Intisari Latar Belakang: Buah, kulit dan biji alpukat mengandung metabolit sekunder seperti flavonoid dan tanin yang memiliki aktivitas antioksidan. Namun, penelitian terkait kulit alpukat sebagai antioksidan belum banyak dilakukan.Tujuan: Mengetahui aktivitas antioksidan total flavonoid, total tanin ekstrak etanol kulit alpukat.Metode: Buah alpukat yang diperoleh dari Lubuk Linggau, Sumatra Selatan diekstraksi dengan cara maserasi dengan pelarut etanol. Ekstrak kemudian dianalisis kualitatif untuk mengetahui kandungan flavonoid menggunakan Mg dan HCl dan tanin menggunakan FeCl3. Penentuan aktivitas antioksidan ekstrak dilakukan dengan metode DPPH, sedangkan penentuan flavonoid total menggunakan AICI3 serta tanin total menggunakan reagen folin ciocelteu yang diukur menggunakan spektrofotometer UV-VIS. Hasil: Hasil analisis kualitatif memperlihatkan bahwa ekstrak etanol kulit alpukat mengandung flavonoid dan tanin. Esktrak etanol kulit alpukat memiliki aktivitas antioksidan kuat dengan IC50 41,93 µg/mL. Kandungan flavonoid total dan tanin total ekstrak etanol kulit alpukat masing-masing adalah 125,01 mgQE/g ekstrak dan 53,82 mgTAE/g ekstrak.Kesimpulan: Ekstrak etanol kulit alpukat memiliki aktivitas antioksidan dengan kandungan flavonoid yang lebih tinggi dibandingkan tanin.Katakunci: antioksidan, DPPH, flavonoid total, tanin total